Stimulation of Bladder Acupoints by Cloprostenol for Treating Back Soreness in Athletic Horses - Eldessouky Sheta; Haithem Farghali; Safwat Ragab; Nagwa Hassan; Asmaa El-Sherif (Medical Association of Pharmacopuncture Institute, 2019)
Twenty-five Thoroughbred jumper geldings suffered back soreness with poor performance, and 5 control horses were assessed by archived computer data, clinical examination, and laboratory analyses of complete blood picture, serum enzymes, and cortisol level, before and after cloprostenol-pharmacopuncture. The 25 diseased horses before therapy showed significant increases in aspartate aminotransferase and creatine phosphokinase with clinical pains scored mild in 15 horses, moderate in 9 horses, and severe in one horse, without changes in the hormonal and hematological data. After therapy, they responded by an increase of heart rate (57.8 ± 4.3 bpm), body temperature (38.5 ± 0.7°C), respiration rate (28.3 ± 2.1 bpm), and capillary refilling time (CRT) (1.0 ± 0.0). On the 2nd day, a significant decrease in the mean levels of aspartate aminotransferase and creatine phosphokinase (P = 0.001) was detected, while on the 4th day, they mimed the level of the 5 controls, and on the 6th day, they showed a significant decrease (P = 0.002). The serum cortisol level showed a significant increase on the 6th day of treatment (P = 0.013). The blood picture showed significant increases in red blood cells, mean corpuscular volume, platelets, white blood cells, hemoglobin, mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration, mean platelet volume, platelet distribution width, lymphocytes, plateletcrit, and large platelet concentration ratio (P < 0.05) and nonsignificant changes in hematocrit, granulocytes, and midocytes. The improved blood parameters, enzymes, hormones, and performance progress after cloprostenol-pharmacopuncture proved its effectiveness in treating back soreness in athletic horses. Keywords: athletic horses, pharmacopuncture, back soreness, bladder acupoints, cloprostenol